PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA GURU TERHADAP MUTU PENDIDIKAN SEKOLAH - SUHENRIK P (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
This research aims to know the effect of organizational culture and work motivitation of teacher on the quality of school education. This research was designed using quantitative approach conducted at SMP Negeri I Balusu Kabupaten Toraja Utara, South Sulawesi. The sample of this research was 32 respondents. The result of this research shows that organizational culture and work motivation of teacher have positive effect on the quality of school education. This result reveals that organizational culture and work motivation of teacher can lead into the increase of the quality of education.